The role of antimicrobial stewardship in curbing carbapenem resistance. (August 2013) - Bogan, Christopher; Marchaim, Dror
Antimicrobial resistance is a continuing, growing, worldwide iatrogenic complication of modern medical care. Carbapenem resistance among certain pathogens poses a significant challenge. In order to reduce the spread of these nearly untreatable pathogens, preventative efforts should be directed at reducing patient-to-patient transmission and preventing the emergence of resistance among susceptible strains. One theoretical intervention to reduce the emergence of resistance is establishing and strictly adhering to an antimicrobial stewardship program. However, data pertaining to the direct effect of stewardship in curtailing carbapenem resistance among epidemiologically significant organisms are scarce. In this report, we review the potential biases associated with data interpretation in this research field, and we review the data pertaining to the impact of stewardship in curbing carbapenem resistance in three significant groups of pathogens: Pseudomonas aeruginosa, Enterobacteriaceae and Acinetobacter baumannii.